Southern African guidelines for the safe use of pre-exposure prophylaxis in men who have sex with men who are at risk for HIV infection - Southern African HIV Clinicians Society Consensus Committee (AOSIS, 2012)
Background. The use of oral antiretrovirals to prevent HIV infection among HIV-negative men who have sex with men (MSM) has been shown to be safe and efficacious. A large, randomised, placebo-controlled trial showed a 44% reduction in the incidence of HIV infection among MSM receiving a daily oral fixed-dose combination of tenofovir disoproxil fumarate and emtricitabine (Truvada) in combination with an HIV prevention package. Improved protection was seen with higher levels of adherence. Aim. The purpose of this guideline is to: (i) explain what pre-exposure prophylaxis (PrEP) is; (ii) outline current indications for its use; (iii) outline steps for appropriate client selection; and (iv) provide guidance for monitoring and maintaining clients on PrEP. Method. PrEP is indicated for HIV-negative MSM who are assessed to be at high risk for HIV acquisition and who are willing and motivated to use PrEP as part of a package of HIV prevention services (including condoms, lubrication, sexually transmitted infection (STI) management and risk reduction counselling). Recommendations. HIV testing, estimation of creatinine clearance and STI and hepatitis B screening are recommended as baseline investigations. Daily oral Truvada, along with adherence support, can then be prescribed for eligible MSM. PrEP should not be given to MSM with abnormal renal function, nor to clients who are unmotivated to use PrEP as part of an HIV prevention package; nor should it be commenced during an acute viral illness. Three-monthly follow-up visits to assess tolerance, renal function, adherence and ongoing eligibility is recommended. Six-monthly STI screens and annual creatinine levels to estimate creatinine clearance are recommended. Hepatitis B vaccination should be provided to susceptible clients. Gastro-intestinal symptoms and weight loss are common side-effects, mostly experienced for the first 4 - 8 weeks after initiating PrEP. There is a risk of the development of antiretroviral resistance among those with undiagnosed acute HIV infection during PrEP initiation and among those with sub-optimal adherence who become HIV infected while on PrEP. Risk compensation (increasing sexual behaviours that can result in exposure to HIV) while on PrEP may become a concern, and clinicians should continue to support MSM clients to continue to use condoms, condom-compatible lubrication and practice safer sex. Research is ongoing to assess optimum dosing regimens, potential long-term effects and alternative PrEP medications. Recommendations for the use of PrEP among other at-risk individuals, and the components of these recommendations, will be informed by future evidence. S Afr J HIV Med 2012;13(2):40-55.